Translating Expressive Language: Some Socio-Cultural Insights - Katarina Gjurchevska Atanasovska and Sonja Kitanovska-Kimovska (My University, 2022)
Expressive lexical units are culturally bound and deeply rooted into socio-cultural contexts; their connotative dimension accentuates their implicit meaning dependent on extralingustic factors which are related to cultural notions and ways of using them within a society. The purpose of this paper is to show that contrastively analysing expressive language in translation can shed light on some interesting insights into socio-cultural similarities and differences between English and Macedonian with regard to certain types of expressive language. The results of the survey confirm that differences in socio-cultural and historical conditions have differently affected the ways in which concepts and notions are perceived in these languages, leading to differences in the use of expressive words and their metaphorical dimension in both languages and posing challenges to translators.
Keywords: language, culture, translation, society, expressive language